2016
DOI: 10.3389/fpls.2016.00384
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Transcript Related to Osmosis and Intracellular Ion Homeostasis in Paulownia tomentosa under Salt Stress

Abstract: Paulownia tomentosa is an important economic and greening tree species that is cultivated widely, including salt environment. Our previous studies indicated its autotetraploid induced by colchicine showed better stress tolerance, but the underlying molecular mechanism related to ploidy and salt stress is still unclear. To investigate this issue, physiological measurements and transcriptome profiling of diploid and autotetraploid plants untreated and treated with NaCl were performed. Through the comparisons amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…Xiong found that the over-expression of MYB48-1 promoted biosynthesis of ABA and improved drought resistance of transgenic rice [29]. AtMYB60 regulated stomatal movement and promoted Arabidopsis thaliana to respond to drought stress [66]. Different MYBs showed varied functions in the progress of responding to drought and improved drought resistance.…”
Section: Expressions Of Genes Responding To Iaa and Tf Genes Under Pementioning
confidence: 99%
“…Xiong found that the over-expression of MYB48-1 promoted biosynthesis of ABA and improved drought resistance of transgenic rice [29]. AtMYB60 regulated stomatal movement and promoted Arabidopsis thaliana to respond to drought stress [66]. Different MYBs showed varied functions in the progress of responding to drought and improved drought resistance.…”
Section: Expressions Of Genes Responding To Iaa and Tf Genes Under Pementioning
confidence: 99%
“…Our studies found that both exogenous IAA and drought stressregulated expression of MYB14 and MYB48 and L-AOPP decreased their expressions (Figure 4G, 4H).Xiong found that the over-expression of MYB48-1 promoted biosynthesis of ABA and improved drought resistance of transgenic rice[30]. AtMYB60 regulated stomatal movement and promoted Arabidopsis thaliana to respond to drought stress[67]. Different MYBs showed varied functions in the progress of responding to drought and improved drought resistance.…”
mentioning
confidence: 62%
“…bZIP37 expressed highly in the salt-stressed plant, which might effectively activated downstream of ABA-inducible gene expression [64]. We found that expression of bZIP11 was also induced by exogenous IAA (Figure 4A), and that of bZIP37 was induced by PEG-6000 stress ( Figure 4B).…”
Section: Changes Of Expression Of Genes Responsing To Iaa and Tf Genesmentioning
confidence: 86%